Post spinal anaesthesia shivering- incidence and associated risk factors in patients undergoing lower limb and abdominal surgeries - Kanchan, Swati; Shah, Akif Mutahar; Shah, Aliya; Sameen, Zaka; Arya, Aditya; Riaz, Safura; Zaman, Muzaffar; Santapur, Madhvi (International Journal of Research in Medical Sciences, 2022)
Background: This study was conducted to evaluate the incidence of shivering and likely associated risk factors following spinal anaesthesia in patients undergoing lower abdominal and lower limb surgeries. Methods: The present study was conducted in MMIMSR, Department of anaesthesia from December 2016 to September 2018. It was an observational study which was conducted over a period of 2 years. Patients who were scheduled to undergo elective lower abdominal and lower limb surgeries under spinal anaesthesia were included in study. Results: The present study depicts a high incidence of post spinal shivering, which was 42.8%. Majority of the patients belonged to the young age group between 20-30 years. The mean time of onset of shivering, was around 25 mins. Duration of shivering was observed between 15-75 minutess with a mean of 43.75 and SD±19.39. Conclusions: Shivering is one of the distressing complications of spinal block, which may be deleterious to the patients with poor cardio-respiratory reserve.